Post-transplant idiopathic non-lupus full-house nephropathy – A case report (Indian Journal of Case Reports, 2022)
We report a case of Idiopathic non-lupus full-house nephropathy (NLFHN) in a 39-year-old male who had a full-house pattern of immunofluorescence study without overt systemic lupus erythematosus after a follow-up of more than 2 years. The incidence of detection of cases of NLFHN is increasing in native kidney biopsy and is critical to report as they have poor clinical outcomes. To the best of our knowledge, it is the first case of post-transplant renal biopsy and needs to be reported to plan the treatment protocol for such transplant patients.